The Cytosolic Chaperonin CCT/TRiC and Cancer Cell Proliferation - Boudiaf-Benmammar, Chafika (Public Library of Science, 2013)
The molecular chaperone CCT/TRiC plays a central role in maintaining cellular proteostasis as it mediates the folding of the major cytoskeletal proteins tubulins and actins. CCT/TRiC is also involved in the oncoprotein cyclin E, the Von Hippel-Lindau tumour suppressor protein, cyclin B and p21(ras) folding which strongly suggests that it is involved in cell proliferation and tumor genesis. To assess the involvement of CCT/TRiC in tumor genesis, we quantified its expression levels and activity in 18 cancer, one non-cancer human cell lines and a non-cancer human liver. We show that the expression levels of CCT/TRiC in cancer cell lines are higher than that in normal cells. However, CCT/TRiC activity does not always correlate with its expression levels. We therefore documented the expression levels of CCT/TRiC modulators and partners PhLP3, Hop/P60, prefoldin and Hsc/Hsp70. Our analysis reveals a functional interplay between molecular chaperones that might account for a precise modulation of CCT/TRiC activity in cell proliferation through changes in the cellular levels of prefoldin and/or Hsc/p70 and CCT/TRiC client protein availability. Our observation and approaches bring novel insights in the role of CCT/TRiC-mediated protein folding machinery in cancer cell development.